(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Personalities who are well known in public because of their credibility and the work they do is known as celebrity. Advertisers are using celebrity to enhance the effectiveneness and influence of their commercials. Previous research has also proven the fact the celebrity endorsement plays a very important role in influencing consumer. A global study of tv advertising also found out that celebrity endorsing a TV ad is common on every continent. The present study is an attempt to outline how celebrity endorsement leads to purchase Intention towards the endorsed brand. The study was conducted on a sample of 150 respondents residing in and around Bangalore city using non-probability sampling method. Structural equation modeling (SEM) was applied to understand the relationship between Celebrity Endorsement, Attitude towards Ad, Brand credibility, and Attitude towards brand and its influence on purchase intention. Results endorse the fact that celebrity does play a significant role in influencing the audience positively The study also show the way audience receive, associate and identify the product and finally get influenced by celebrity endorsement and how celebrity endorsement in advertisement as a tool affects and influence people opinion in marketing.